Resonance-like structure observed in ²⁵Mg(p; γ)²⁶Al reaction - Kachan, A.S.; Kurguz, I.V.; Mischenko, V.M.; Utenkov, S.N. (Вопросы атомной науки и техники, 2017)
The γ decay of the resonance-like structure (RLS), observed in the ²⁵Mg(p; γ)²⁶Al in the region of excitation energies of 7...9 MeV was studied. The excitation function of the ²⁵Mg(p; γ)²⁶Al reaction was measured. The resonance strengths in the accelerated proton energy range of Eₚ = 1.4...2.0 MeV were determined. The obtained distributions of the strength of M1 transitions between the resonance states and the low-lying bound states in ²⁶Al have resonance character. The position of the center of gravity of the magnetic dipole resonance (MDR) on the ground state is equal to 7.92 MeV . Total strength MDR in ²⁶Al is equal to 5.7 MeV μ²ₙ.